New Experimental Rig to Investigate Abrasive–Corrosive Characteristics of Metals in Aqueous Media - Salasi, Mobin; Stachowiak, Grazyna; Stachowiak, G. (Springer, 2010)
A new tribometer to investigate a conjoint effect of three-body abrasion and corrosion has been developed. In this design, a flat wear sample is loaded against a rotating cylindrical disc counterface and the abrasive slurry is delivered to the contact interface. Capabilities of the newly developed tribometer have been assessed through conducting abrasion–corrosion tests involving simultaneous electrochemical measurements. In this work, the stability of the passive layer on stainless steel under three-body abrasive wear in a near neutral electrolyte was investigated using potentiodynamic polarization tests. 316L Stainless Steel wear samples were abraded by coarse garnet particles in an aerated sodium sulphate electrolyte. The effects of load and speed on the polarization curves and passivity of 316L steel were determined. It was found that under abrasion–corrosion conditions 316L steel became more thermodynamically active and the passive corrosion rate has increased. Increasing the contact load resulted in a small increase in the passive corrosion current, while increasing the rotating speed had the opposite effect of decreasing the current. Linear polarization resistance method was used to analyse corrosion current changes with time during abrasion–corrosion testing. The existence of three distinct stages was explained by the third-body effect on the corrosion potential and current.First stage was revealed by continuous decrease of corrosion potential. Then, the potential reached a plateau for the second and third stages. In the first and second stages, particle constraint in the contact zone plays the major role and a linear rise in corrosion current with time has been recorded. After a certain amount of surface roughening, no further increase in particles entrapment is expected. Therefore, in the third stage steady-state corrosion current values are anticipated. The rig developed can also be used to simulate two-body abrasion–corrosion. The capabilities of the new rig have been compared against other experimental set-ups used in studies of combined abrasion–corrosion behaviour.